The Role of Product and Service Quality in A Competitive Position: Depositors’ Satisfaction - Jusni Jusni; Andi Aswan; Gunawan Baharuddin; Hafizah Abdul Rahim (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2022)
AbstractThe study seeks how the Regional Development Banks operating in South and West Sulawesi maintain and attract depositors by evaluating the deposit products and banking service quality that have an impact on depositors' satisfaction. The study collected data using questionnaires distributed to 100 depositors owned by three Regional Development Banks. The data collected is then used to analyze the constructs of savings products, quality of banking services, and satisfaction using factor analysis to ensure that the five indicators proposed for each construct are eligible to be analyzed using the Structural Equation Model (SEM) method. The study found that the construction of deposit products and service quality have a positive impact on depositors' satisfaction with a dominant impact on deposit products. Banking service quality delivered by RDBs can attract deposit consumers as they have already convenience with the products and service quality Keywords:Product Quality, Product Features, Service Quality, Depositors’ Satisfaction Peran Produk dan Kualitas Layanan dalam Daya Saing: Studi Kasus tentang Kepuasan Nasabah AbstrakPenelitian ini mengumpulkan data 100 simpanan pada tiga Bank Pembangunan Daerah. Data yang terkumpul kemudian digunakan untuk menganalisis konstruk produk tabungan, kualitas layanan perbankan, dan kepuasan menggunakan analisis faktor untuk memastikan bahwa kelima indikator yang diajukan untuk setiap konstruk memenuhi syarat untuk dianalisis menggunakan metode Structural Equation Model (SEM). Temuan menunjukkan bahwa, kecuali daya tanggap untuk konstruk kualitas layanan perbankan, semua variabel terukur dikatakan dapat mendefinisikan konstruknya. Lebih lanjut, konstruksi produk simpanan dan kualitas layanan berpengaruh positif terhadap kepuasan nasabah dengan dampak dominan terhadap produk simpanan. Artinya, fitur-fitur yang ditawarkan dan kualitas layanan perbankan yang diberikan oleh BPD dapat menarik minat nasabah simpanan karena sudah memiliki kemudahan dengan kualitas produk dan layanan.. Kata kunci: Kualitas produk, fitur produk, kualitas pelayanan, kepuasan nasabah.